Espectroscopia de reflectância in vivo do líquen escleroso vulvar - Guedes, Guelton Hirano (2018)
Diffuse reflectance spectroscopy was used in vivo to compare treatments with corticosteroid (COR), photobiomodulation (PBM) and photodynamic therapy (PDT) in vulvar lichen sclerosus (VLS). Fifteen patients were recruited at the outpatient clinic of Pérola Byington Hospital. They were divided into three groups of five patients each and treated for one month. Reflectance spectra were collected from two regions of vulvar skin of each patient, one with VLS and one without. Also, the absorbance spectra were determined from the diffuse reflectance spectra. The data were analyzed using the statistical softwares Origin® Pro 8 and Minitab® 18. The reflectance spectra were smoothed by Savitzky-Golay method and integrated. The areas under the curves were submitted to the Kolmogorov-Smirnov normalit y test and to the Levene test of homogeneity of variances. The comparison between the groups was performed using Generalized Linear Models (GLM) test, having as cofactors age, time of pruritus and Fitzpatrick scale. All statistical significance was 𝛼 = 0.05. There were no differences between treatments before and after one month of treatment. By means of the apparent absorbance spectra, it has been observed that there are maximum points in two bands. The first has a maximum point at 𝜆1 = (422.6 ± 5.4) 𝑛𝑚 and the second, at 𝜆2 = (492.6 ± 3.1) 𝑛𝑚, which may be related to the Soret absorption band of oxyhemoglobin (412 𝑛𝑚), deoxyhemoglobin (430 𝑛𝑚) or bilirubin (460 𝑛𝑚). By means of the linear regression coefficient of the natural logarithm of the ratio between the diffuse reflectance spectra of the region with VLS and that of the non-VLS region, it was verified that the patient of the FBM group had the lowest reduction in the concentration of melanin, in the order of 2.8%, while that of the COR group had a reduction of 81.7% and that of the PDT group, 73,8%, of reduction in the melanin concentration.